Health Related Quality of Life of Oral Cancer Patients Who Receive Radiotherapy With or Without Chemotherapy in Sri Lanka - Shamini Kosgallana; Prasanna Jayasekara; Prasad Abeysinghe; Ratilal Lalloo (Journal of Multidisciplinary Dental Research)
Patient reported health related quality of life outcomes have considered as valid information when deciding the treatments and making protocols in cancer management. The aim of the study was to assess the health-related quality of life of oral cancer patients who receive radiotherapy (RT) with or without chemotherapy and the changes in health-related quality of life. A prospective study was conducted among 90 oral cancer patients who receive RT with or without chemotherapy. Two European Organization for the Research and Treatment of Cancer Quality of Life Questionnaires: EORTC QLQ-C30 and EORTC QLQ-H&N35, were used to assess health-related quality of life before RT, during the last week of RT and three months after RT. The majority were males (88%) and 68% were aged 50-69. The median scores of all the domains and items in EORTC QLQ-H&N35 and symptom domains and items in EORTC QLQ-C30 were higher during the last week of RT compared to the baseline (most scores were zero). Except for ‘Appetite loss’ item, all the symptom domains and items scores were lower at three months after RT than the median scores during last week of RT. Statistically significant differences were observed in almost all the changes in health-related quality of life between three time frames (p<0.05). Health-related quality of life of oral cancer patients declined due to RT from baseline to the last week of RT and improved three months after RT from last week of RT but had not returned to the baseline level. Keywords: Oral cancer, Health related quality of life, Radiotherapy, EORTC QLQ-H&N35, EORTC QLQ-C30